Hubungan Post Traumatic Growth Dengan Kualitas Hidup Pada Anak Usia Sekolah Yang Sedang Menjalani Palliative Care - Canissa Ajeng Rafiska; Siti Lestari; Muhammad Anis Taslim (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Chronic disease in children requires long-term care because of the prognosis and development of the disease. Chronic illness is not an easy thing for children and parents to deal with. Children undergoing medical and nursing care are scary things, these conditions require them to adapt to new routines that are part of their lives every day. This condition can be categorized as a traumatic event, which can affect psychological changes. These psychological changes are called post traumatic growth. Changes in these conditions become one of the factors that affect the quality of life. This study aims to determine the relationship between post traumatic growth and the quality of life of school-age children who are undergoing palliative care. This type of quantitative research with cross sectional approach method. The sampling technique used was purposive sampling with a sample size of 63 respondents. Based on the results of the Sperm- rank statistical test, a p-value of 0.013 was obtained with a positive correlation with a result of 0.312, so that it can be interpreted that there is a relationship between post traumatic growth and the quality of life of school-age children undergoing palliative care. Suggestions to parents or families are expected to always pay attention to physical and psychological conditions, as well as provide motivation and enthusiasm in undergoing palliative care so as to improve the quality of life in patients after experiencing a post traumatic growth process.